Standardization of Inoculation method for F. oxysporum f.sp. melonis - PUSHPINDER P. SINGH*, RUPINDER K. SEKHON and (Indian Phytopathology, 2009)
Method of inoculation exerted significant influence on the development of muskmelon wilt caused by Fusarium oxysporum f. sp. melonis. Maximum disease incidence was recorded when muskmelon seeds (cv. Pb. Sunehri) were sown in the soil inoculated with mass inoculum of F. oxysporum f. sp. melonis. Other methods, which involve pipetting mass inoculum to the undisturbed seedlings or dipping seedling roots into inoculum suspension delivered inconsistent results. Therefore, direct sowing of muskmelon seeds in artificially inoculated soil (soil inoculum added @ 2.5g/100g of soil) was better (D.I. = 98.3%) than all other methods of inoculation viz. transplanting of seedlings in artificially inoculated soil, root dip method and pipette method. For all inoculation methods, less disease incidence was observed when seedlings were inoculated two weeks after planting than one week after planting.